Preschoolers Flexibly Shift Between Speakers' Perspectives During Real‐Time Language Comprehension. Issue 3 (20th June 2019) - Khu, Melanie; Chambers, Craig G.; Graham, Susan A.
Abstract : In communicative situations, preschoolers use shared knowledge, or "common ground, " to guide their interpretation of a speaker's referential intent. Using eye‐tracking measures, this study investigated the time course of 4‐year‐olds' ( n = 95) use of two different speakers' perspectives and assessed how individual differences in this ability related to individual differences in executive function and representational skills. Gaze measures indicated partner‐specific common ground guided children's interpretation from the earliest moments of language processing. Nonegocentric online processing was positively correlated with performance on a Level 2 visual perspective‐taking task. These results demonstrate that preschoolers readily use the perspectives of multiple partners to guide language comprehension and that more advanced representational skills are associated with the rapid integration of common ground information.